Dynamical ground state in the XY pyrochlore Yb2GaSbO7 - P. M. Sarte; K. Cruz-Kan; B. R. Ortiz; K. H. Hong; M. M. Bordelon; D. Reig-i-Plessis; M. Lee; E. S. Choi; M. B. Stone; S. Calder; D. M. Pajerowski; L. Mangin-Thro; et al. (npj Quantum Materials, 2021)
Abstract The magnetic ground state of the pyrochlore Yb2GaSbO7 has not been established. The persistent spin fluctuations observed by muon spin-relaxation measurements at low temperatures have not been adequately explained for this material using existing theories for quantum magnetism. Here we report on the synthesis and characterisation of Yb2GaSbO7 to revisit the nature of the magnetic ground state. Through DC and AC magnetic susceptibility, heat capacity, and neutron scattering experiments, we observe evidence for a dynamical ground state that makes Yb2GaSbO7 a promising candidate for disorder-induced spin-liquid or spin-singlet behaviour. This state is quite fragile, being tuned to a splayed ferromagnet in a modest magnetic field μ 0 H c ~ 1.5 T.